Impact of biological and artificial seminal fluids on sperm parameters and DNA status in asthenozoospermic ejaculates. (4th March 2021) - Gholizadeh, Lida; Agha‐Rahimi, Azam; Ghasemi‐Esmailabad, Saeed; Maleki, Behnam; Ahamed, Abdul Munaf Sultan; Khalili, Mohammad Ali
Abstract: The chemical composition and physiological properties of seminal fluid (SF) affect sperm quality. The objective was to investigate the effects of in vitro exposure of artificial seminal fluid (ASF) and biological seminal fluid (SF) on sperm quality. Asthenozoospermic ejaculates ( n = 20) were divided into two aliquots. The first aliquot was centrifuged for obtaining asthenozoospermic SF. The second aliquot was processed with density gradient centrifugation (DGC), and the pellet was diluted separately with following media: (a) ASF; (b) Ham's F10; (c) normozoospermic SF; and (d) asthenozoospermic SF. Sperm parameters and DNA status were assessed after DGC, as well as 2 and 24 hr after incubation. The data showed that sperm progressive motility, viability and DNA integrity were significantly higher in ASF than Ham's F10 medium immediately after DGC. At 2 and 24 hr, the progressive motility was significantly decreased in biological SF compared with ASF and Ham's F10. DNA fragmentation index (DFI) was significantly lower in normozoospermic SF than asthenozoospermic SF and Ham's F10 at time 2 hr. In conclusion, normal SF showed the protective role on sperm DNA structure. Moreover, ASF preserved sperm motility better than biological SF during 24 hr, despite being similar to normal SF regarding DNA integrity preservation in short time.